Study and thinking skills : an English skills text for general communication task - Infante Dennis G.; Dulalas-Diongon, May M.; Colle, Arnold M. (Quezon City : C & E Publishing, 2009)
Includes references.
Keywords: English language -- Textbooks for foreigners -- Philippines